Antiproliferative and Antioxidant Properties of Anthocyanin Rich Extracts from Blueberry and Blackcurrant Juice - Diaconeasa, Zoriţa (Int J Mol Sci, 2015)
The present study was aimed at evaluating the antiproliferative potential of anthocyanin-rich fractions (ARFs) obtained from two commercially available juices (blueberry and blackcurrant juices) on three tumor cell lines; B16F10 (murine melanoma), A2780 (ovarian cancer) and HeLa (cervical cancer). Individual anthocyanin determination, identification and quantification were done using HPLC-MS. Antioxidant activity of the juices was determined through different mechanism methods such as DPPH and ORAC. For biological testing, the juices were purified through C(18) cartridges in order to obtain fractions rich in anthocyanins. The major anthocyanins identified were glycosylated cyanidin derivatives. The antiproliferative activity of the fractions was tested using the MTT assay. The antiproliferative potential of ARF was found to be associated with those bioactive molecules, anthocyanins due to their antioxidant potential. The results obtained indicated that both blueberry and blackcurrants are rich sources of antioxidants including anthocyanins and therefore these fruits are highly recommended for daily consumption to prevent numerous degenerative diseases.